Antiplasmodials soulattrolide derivatives from Calophyllum brasiliense and its mechanism of activity (2019)
Parasitic diseases such as malaria, leishmaniasis, trypanosomiasis, and schistosomiasis are just one of the main causes of disease and death in the world today (WHO, 2016). In 2016, 91 countries reported a total of 216 million cases of malaria, which represents an increase to 5 million cases in relation to the previous year, with 15 countries holding 80% of the global burden of malaria. The total number of deaths worldwide reached 445.000, similar to that reported in 2015 (WHO, 2017; Chin, 2001; Newman et al., 2016), so there is an urgent need to discover new, safe and effective drugs for the prophylaxis and treatment of malaria, mainly due to the development of resistance of Plasmodium falciparum, the most lethal Plasmodium species to chloroquine and other antimalarial drugs. Few alternative drugs are in development and urgent measures are needed to identify new types of antimalarial agents, many of which have originated from natural products (Olumese, 2015; Leach, 2001). Clusiaceae is one of the families of plants in which compounds with antimalarial activity have been found, such as xanthones and derivatives of acylphloroglucinol. Since the genus Calophyllum is a potential source of secondary metabolites and its species are little explored in the field of malaria, their exploration is justified as a phytotherapeutic alternative in the treatment of malaria (Hay et al., 2004; Chanphen et al., 1998; Pierson et al., 2010; Guillaume et al., 2009). This paper reports the isolation of soulattrolide (1) from C. brasiliense. the preparation of eight new derivatives (2–9) by hemi-synthesis and the bioactivity studies thereof. [Tomado de la introducción]